Thallium-based high-temperature superconductors - Hermann, Allen M.; Yakhmi, J.V (Marcel Dekker, 1994)
Provides information on all chemical, physical and material aspects of this class of cuprates, and covers their applications. This work provides data on the chemistry, solid-state chemistry, handling and safety requirements of thallium.